2016
DOI: 10.18632/oncotarget.10182
|View full text |Cite
|
Sign up to set email alerts
|

Virus infection facilitates the development of severe pneumonia in transplant patients with hematologic malignancies

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is an effective therapy for patients with hematologic malignancies. Severe pneumonia is associated with high mortality rate in HSCT recipients. Viral co-infection indicates a poor prognosis of HSCT recipients. In this study, a total of 68 allogeneic HSCT recipients were included. Cytomegalovirus (CMV) and Respiratory syncytial virus (RSV) infection was assessed by testing peripheral blood and oropharynx swabs, respectively, collected in the first 180 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Another relevant finding of this study was the identification of 3 RFs for mortality easily identifiable at the time of CARVs LRTD. These RFs have already been identified as prognostic markers for progression to LRTD (ie, lymphopenia) in several studies among different respiratory virus or as RFs for mortality (ie, lymphopenia <0.5 × 109/L, oxygen requirement, and CMV DNAemia‐RAT) . With these 3 RFs we built a risk score that was able to discriminate 3 groups with different risk of mortality irrespective of the co‐infective status that merit to be validated in further studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Another relevant finding of this study was the identification of 3 RFs for mortality easily identifiable at the time of CARVs LRTD. These RFs have already been identified as prognostic markers for progression to LRTD (ie, lymphopenia) in several studies among different respiratory virus or as RFs for mortality (ie, lymphopenia <0.5 × 109/L, oxygen requirement, and CMV DNAemia‐RAT) . With these 3 RFs we built a risk score that was able to discriminate 3 groups with different risk of mortality irrespective of the co‐infective status that merit to be validated in further studies.…”
Section: Discussionmentioning
confidence: 98%
“…First, our study showed that bacterial co‐infection had a significant negative effect on clinical outcome in contrast to respiratory virus and IA co‐infections. Second, there is an increased evidence in the mechanism whereby viral infections enhance and aggravate bacterial co‐infection, the former favoring the growth of bacterial agents by multiple factors, including local destruction of antibacterial barriers at epithelial surfaces, suppression of antibacterial immunity, and induction of apoptosis in immune cells . Third, RFs for respiratory virus co‐infection are expected to be different from those affecting bacterial co‐infection since respiratory virus transmission depend upon epidemiologic situation such as the recipients house‐hold contacts, contact with children, vaccination status, which has not been captured in our data base.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with hematological malignancies or prior HSCT, lymphocytopenia was significantly associated with serious CMV pneumonia [5] which leads more frequently to death than other infections. In fact, Caifeng Yue et al showed that CMV and respiratory syncytial virus (RSV) co-infection facilitates the development of severe pneumonia [58]. Direct herpesvirus mediated tissue injury (e.g.…”
Section: Discussionmentioning
confidence: 99%